Programas de transferência de renda: uma análise do auxílio emergencial - Arena, Rafael (2021)
The study aims to analyze the impact of the beneficiary profile variables for the destination of resources received through cash transfer programs. Using a database of 3 million beneficiaries of Auxílio Emergencial (emergency aid), a cash transfer program created by the Brazilian government to mitigate the economic effects of sanitary measures during the COVID 19 epidemic in the period from April 2020 to January 2021, we found that age and gender are significant in determining the share allocated by beneficiaries for essential expenditures. The results found can help public agents to improve the allocation of resources in income transfer programs through the adequacy of qualification criteria, thus seeking greater efficiency in the expenditure of public policies of a social nature.